(untitled) (Salam International Academic Journal, 2023)
Artificial Intelligence (AI) is a significant phenomenon in the realm of technology, having wrought transformative changes across global industries and our daily lives. This research paper delves into the multifaceted domain of AI, encompassing its historical evolution, its profound impact on industries, its merits, drawbacks, dispelling common misconceptions, and an exploration of various AI language models. Moreover, we scrutinize the inherent limitations of these models and offer insights into the evolving technological landscape, along with glimpses into the potential future trajectories. For those seeking a comprehensive understanding of the dynamic tech landscape, this paper provides essential insights.